Quintijn Mauer, Application, Adaptation and Rejection. The strategies of Roman jurists in responsa concerning Greek documents (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2023)
Quintijn Mauer, Application, Adaptation and Rejection. The strategies of Roman jurists in responsa concerning Greek documents, Bodegraven, AlphaZet prepress, 2022, pp. XV + 285. ISBN: 978-94-6236-291-8